INFLUENCE OF INVESTMENT RISK, KNOWLEDGE, AND ALLOWANCE ON STUDENTS' INVESTMENT INTEREST - ZUHROHTUN, ZUHROHTUN; Halim, Angsol Taffagani; Kusumawardhani, Indra (Buletin Studi Ekonomi; VOLUME.29.NO.02.TAHUN.2024DO - 10.24843/BSE.2024.v29.i02.p08, 2024)
The study empirically examines the effect of investment risk, investment knowledge, and student allowance on student interest in investing in the capital market. This research uses a survey method. The research respondents were 105 students of the Faculty of Economics and Business UPN "Veteran" Yogyakarta.  The sample selection method is random sampling. The hypothesis was tested with multiple regression analysis. The results prove that investment risk has a negative influence on student interest in investing in the capital market, and investment knowledge, and student pocket money have a positive effect on student interest in investing in the capital market.